Effect of manganese ions on ethanol fermentation by xylose isomerase expressing Saccharomyces cerevisiae under acetic acid stress - Ko, Ja Kyong; Um, Youngsoon; Lee, Sun-Mi (Elsevier BV, 2016)
The efficient fermentation of lignocellulosic hydrolysates in the presence of inhibitors is highly desirable for bioethanol production. Among the inhibitors, acetic acid released during the pretreatment of lignocellulose negatively affects the fermentation performance of biofuel producing organisms. In this study, we evaluated the inhibitory effects of acetic acid on glucose and xylose fermentation by a high performance engineered strain of xylose utilizing Saccharomyces cerevisiae, SXA-R2P-E, harboring a xylose isomerase based pathway. The presence of acetic acid severely decreased the xylose fermentation performance of this strain. However, the acetic acid stress was alleviated by metal ion supplementation resulting in a 52% increased ethanol production rate under 2 g/L of acetic acid stress. This study shows the inhibitory effect of acetic acid on an engineered isomerase-based xylose utilizing strain and suggests a simple but effective method to improve the co-fermentation performance under acetic acid stress for efficient bioethanol production. (C) 2016 Elsevier Ltd. All rights reserved.